A Preliminary First Principle Study on Photochromism of Diarylethene Molecules - Karki, Ravi (Prithvi Journal of Research and Innovation, 2019)
Photochromism in some diarylethene molecules have been studied by using hybrid density functional theory using the ground state energy consideration. In particular, B3LYP functional and all electron basis set 6-311G (2d,2p) as implemented in Gaussian09 suites of program has been used to investigate the energy difference of two stable isomers of stilbene, azobenzene, cyclooctane, and 1,2, dimethylcyclohexane molecules. The energy difference is corroborated to calculate the frequencies of photons that are required to induce photochromism in these molecules in vacuum and in solvation state. The study found that the molecules exhibit photochromism at various frequency range from infra-red to ultraviolet. The binding energy per atom, charge distribution, HOMO-LUMO (Highest Occupied Molecular Orbital and Lowest Unoccupied Molecular Orbital) gap are also calculated for all the molecules in vacuum, water and ethanol solvent. The results obtained are in accordance with the experimental observations.